Time Dependent Mathematical Model of Thermoregulation in Human Dermal Parts During Sarcopenia - Shrestha, Dev Chandra; Acharya, Saraswati (Journal of Nepal Mathematical Society, 2021)
Sarcopenia is an illness characterized by the loss of skeletal muscle mass, and its strength occurs in aging after 50 years. Muscle mass plays a vital role in body weight and metabolism. The loses in body weight impact reducing the basal metabolic rate (BMR). The BMR affects the human body temperature due to lower metabolic heat production during sarcopenia. The present study deals with time dependent temperature variation in human dermal parts during sarcopenia. The finite element method is used to solve a one-dimensional bioheat equation. In this model, the thickness of the epidermis, dermis layers, and the BMR of different aging, are estimated. The results show the nodal temperature of the epidermis and dermis layers increases due to reducing the thickness. Further, the subcutaneous nodal temperature slightly decreases due to the cause of BMR.